The Filmmaker's Triage: The Doctor Figure and Images of Trauma. Issue 4 (2nd October 2018) - Kaplan, Kenneth
ABSTRACT: While writing a fictionalised feature film screenplay set around the character of a South African doctor during his year of compulsory community service in a rural hospital, I began researching how this figure has been represented in other narrative films, particularly those stories told in an African setting. A number of films and television dramas, some made by African filmmakers and others by filmmakers from outside of Africa, have been produced around the medical encounter. My interest lies not in assessing the health messaging found in these films and programs, which is better left to the health educationalists and medical sociologists, but in examining the fictional doctor figure as the main protagonist in these films. While the sociocultural and political dimensions of medicine, health and illness are relevant, I refer to them only in passing while exploring the fictional imagery of the doctor figure within the imagined filmed-Africa as it appears in the films The Last Face, Beyond Borders and Le grand blanc de Lambaréné .